(untitled) (Research, Society and Development, 2020)
Know ledge of soil aggregate stability in the region of Cáceres, located in the vicinity of the Pantanal, Cerrado and the Amazon, can assist in making decisions on the adequate soil in these areas. This study aimed to determine the stability of soil aggregates by wet sieving of different methodologies in Red-Yellow Podzolic under native forest in the layer of 0-10 cm. We assessed the distribution of aggregate diameter class, DMP and aggregates content. It wasn’t a significant difference between the methods for the distribution of aggregate diameter class, but was significant among the classes, the class of 9.51 to 4.7 mm had a higher percentage of aggregate, in all treatments. It wasn’t a significant difference between treatments for the DMP. For the content of aggregates was a predominance of aggregates larger than 2 mm (63.22%). In general the soil evaluated can be considered a soil with high aggregate stability.